Update on Eluxadoline for the Treatment of Irritable Bowel Syndrome with Diarrhea: Patient Selection and Perspectives - Liu R; Staller K (Dove Medical Press, 2020)
Rebecca Liu,1 Kyle Staller1,2 1Department of Medicine, Massachusetts General Hospital and Harvard Medical School, Boston, MA, USA; 2Division of Gastroenterology, Department of Medicine, Massachusetts General Hospital and Harvard Medical School, Boston, MA, USACorrespondence: Kyle StallerMassachusetts General Hospital, 165 Cambridge St. 9th floor, Boston, MA 02114-2896, USATel +1 617 724-6038Fax +1 617 726-3080Email kstaller@mgh.harvard.eduAbstract: Irritable bowel syndrome (IBS) is a functional gastrointestinal (GI) disorder characterized by chronic abdominal pain associated with changes in bowel habits. It is the most common GI problem seen by gastroenterologists. IBS is a heterogenous disorder encompassing a spectrum of underlying mechanisms and clinical presentations. The pathophysiology of diarrhea-predominant form of IBS (IBS-D) remains poorly understood, and current available therapeutic options for IBS-D are limited. Eluxadoline is a novel, locally acting mixed μ- and κ-opioid receptor agonist and δ-receptor antagonist approved by the Food and Drug Administration (FDA) for treatment of adults with IBS-D. Data from two phase III clinical trials showed that approximately 25– 30% of the eluxadoline-treated patients achieved composite clinical response, defined by a reduction of abdominal pain and improvement in stool consistency. Patients who achieve composite response during the first month of therapy were significantly more likely to demonstrate sustained clinical response. The most common adverse events reported with eluxadoline use were constipation, nausea and abdominal pain. The risk of abuse, dependence, or withdrawal is low. Serious adverse events associated with eluxadoline include sphincter of Oddi spasm (SOS) and pancreatitis particularly in patients without a gallbladder. Development of pancreatitis is likely secondary to SOS, but it remains unclear why pancreatitis occurs so quickly after initial doses. This adverse event profile helps guide proper selection of IBS-D patients for eluxadoline use, with important contraindications including absence of a gallbladder, biliary duct obstruction or sphincter of Oddi dysfunction, alcoholism, history of pancreatitis, or structural diseases of the pancreas. With the recent clinical trials demonstrating its efficacy, eluxadoline provides an additional option to the few existing pharmacologic interventions available for IBS-D. In this review, we discuss the drug development, efficacy and safety of eluxadoline, as well as selection criteria for identifying appropriate candidates for this medication.Keywords: eluxadoline, efficacy of eluxadoline, irritable bowel syndrome, IBS, irritable bowel syndrome with diarrhea, IBS-D, IBS-D